Creating the Perfect Illusion : What will it take to Create Life-Like Virtual Reality Headsets? - Cuervo, Eduardo; Chintalapudi, Krishna; Kotaru, Manikanta (HotMobile’18, 2018)
As Virtual Reality (VR) Head Mounted Displays (HMD) push the boundaries of technology, in this paper, we try and answer the question, “What would it take to make the visual experience of a VR-HMD Life-Like, i.e., indistinguishable from physical reality?” Based on the limits of human perception, we first try and establish the specifications for a Life-Like HMD. We then examine crucial technological trends and speculate on the feasibility of Life-Like VR headsets in the near future. Our study indicates that while display technology will be capable of Life-Like VR, rendering computation is likely to be the key bottleneck. Life-Like VR solutions will likely involve frames rendered on a separate machine and then transmit-ted to the HMD. Can we transmit Life-Like VR frames wirelessly to the HMD and make the HMD cable-free? We find that current wireless and compression technology may not be sufficient to accommodate the bandwidth and latency requirements. We outline research directions towards achieving Life-Like VR.